Influence of green tea extract on corrosion of different metals in 0.5 mol dm-3 NaCl solution (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The corrosion behavior of copper, aluminum and stainless steel AISI 316L in 0.5 mol dm-3 NaCl solution without and with the addition of an aqueous-ethanol extract of green tea leaves at a temperature of 25°C was investigated. Electrochemical parameters where determined by linear polarization measurements and potentiodynamic polarization method, and the surface of the metal samples were investigated using an optical microscope after the polarization measurements. Results have shown that green tea extract acts as a corrosion inhibitor for copper aluminum and stainless steel.